Exploring Nursing Education Stakeholders’ Perceptions of Students with Disabilities Inclusion in Nursing Education Programs in the United Arab Emirates: Issues and Challenges - DARWISH, AMANI ABDUL RAZZAK (2023)
The purpose of the study was to explore nursing education stakeholders’ perceptions about inclusion of students with disabilities in nursing education programs in the UAE and the barriers and facilitators to their inclusion. A sequential exploratory mixed-methods design was used to conduct this study. Data was collected using unstructured interviews, -semi-structured interviews, and questionnaires. Thematic analysis of the interviews with 7 nursing education stakeholders revealed the following barriers to the inclusion of nursing students with disabilities: 1) Nature of Disability 2) Knowledge of Nursing Faculty 3) Attitudes 4) Communication 5) Resources 6) Nursing Program Requirements 7) Admission and Support Policies 8) Disability Outreach Activities. Semi-structured interviews with 14 nursing education stakeholders showed eight themes related to the facilitators of the inclusion of nursing students with disabilities in nursing education programs: 1) Disability Laws and Policies 2) Disability Awareness 3) Establish Early Detection of Cases 4) Education and Training Programs 5) Creative Access 6) Attitudes 7) Communication to Meet Needs 8) Collaboration with Potential Employers. 284 nursing education students and 29 nursing education faculty members from health science academic institutions in Abu Dhabi, Ajman, Al-Ain, and Al Dhafra in the UAE completed the questionnaires. The descriptive and inferential statistical analysis of the responses of nursing education faculty members and nursing education students was performed using SPSS software. The findings showed that the educators and students had concerns regarding inclusion of students with disabilities. However, implementing facilitators and overcoming barriers can enhance the accessibility of nursing students with disabilities to nursing education programs. The findings also showed significant differences in nursing students' and faculty's perceptions toward inclusion concerning their interactions with students with disabilities and having completed a course about individuals with disabilities. This research fills a knowledge gap related to disability inclusivity in nursing education in the UAE. Understanding the perceptions of nursing education stakeholders towards the inclusion of students with disabilities in nursing education may help in reducing negative attitudes and discriminatory practices and may assist in improving the general understanding of how to increase the participation of students with disabilities in nursing education and the access to care for underrepresented groups. Moreover, the findings of the will support nursing educators in meeting the needs of students with disabilities from legal, ethical and individualistic perspectives. Furthermore, findings will aid nursing education faculty members, nursing education administrators, disability services, and clinical practice partners to determine and provide reasonable accommodations that promote success of nursing students with disabilities in theory and clinical settings, Finally, findings will aid in the revision and subsequent development of policies and guidelines related to educating and supporting students with disabilities in nursing education programs in the UAE.